Minimum effective volume of normal saline for epidural volume extension - Asha Tyagi; Surendra Kumar; Rashmi Salhotra; Ashok Kumar Sethi (Wolters Kluwer Medknow Publications, 2014)
Background: Rescue strategies like changes in tilt of table are used to raise the level of an inadequate sensory block following intrathecal injection. Epidural volume extension (EVE) refers to an injection of normal saline through epidural catheter following an intrathecal block. It results in a rapid increase in the sensory level of subarachnoid block. Thus, it has been postulated that EVE may be used as a rescue strategy for an inadequate post-spinal sensory block. However, the minimum effective volume (MEV) of normal saline for EVE induced increase in level of spinal block has not been researched till date. We proposed to determine the MEV of normal saline required for EVE induced increase in post-spinal block sensory level. Materials and Methods: This prospective sequential allocation study was conducted in consenting adult males after institutional ethical committee approval scheduled for lower limb surgery under combined spinal epidural (CSE) anesthesia, who had an inadequate level of sensory block. Herein, an inadequate level was defined as lower than T 10 at 10 min after the intrathecal injection, with no ascent for two consecutive readings taken 2 min apart. The EVE was performed with normal saline injected through epidural catheter, and was considered successful if the level of sensory block increased by two or more dermatomal segments within 5 min of the injection. The volume of normal saline for EVE was decided by using the up-and-down method, with the first patient receiving 10 mL and a dosing interval of 1 mL in subsequent patients. The analysis was done using the formula of Dixon and Massey, which enabled calculation of the MEV with 95% CI. Quantitative parametric data is represented as mean ± SD and nonparametric data as median (range). Results and Conclusion: The MEV of normal saline to raise the level of sensory block by two or more dermatomal segments within 5 min of EVE is 7.4 mL (95% CI: 5.5-9.9 mL).